Integrated Use Of Inorganic And Organic Fertilizers On Yield Of Wheat In Wheat-T.Aus/Mungbean-T.Aman Cropping Pattern (Bangladesh Journal of Agricultural Research, 2011)
DOI: http://dx.doi.org/10.3329/bjar.v36i3.9282BJAR 2011; 36(3): 543-552